2015
DOI: 10.1152/jn.00917.2014
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic cholinergic modulation of the mouse superior colliculus in vivo

Abstract: The superior colliculus (SC) plays a critical role in orienting movements, in part by integrating modulatory influences on the sensorimotor transformations it performs. Many species exhibit a robust brain stem cholinergic projection to the intermediate and deep layers of the SC arising mainly from the pedunculopontine tegmental nucleus (PPTg), which may serve to modulate SC function. However, the physiological effects of this input have not been examined in vivo, preventing an understanding of its functional r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Stimulation of endogenous release of ACh in the SC in an in vivo preparation demonstrated variability in the magnitude and timescale of this excitatory influence, consistent with both monosynaptic and polysynaptic cholinergic input (Stubblefield et al 2015). These studies suggest that endogenous cholinergic input serves to promote SC-dependent motor output.…”
Section: Cholinergic Input To Superior Colliculus From Parabrachial Rsupporting
confidence: 54%
See 2 more Smart Citations
“…Stimulation of endogenous release of ACh in the SC in an in vivo preparation demonstrated variability in the magnitude and timescale of this excitatory influence, consistent with both monosynaptic and polysynaptic cholinergic input (Stubblefield et al 2015). These studies suggest that endogenous cholinergic input serves to promote SC-dependent motor output.…”
Section: Cholinergic Input To Superior Colliculus From Parabrachial Rsupporting
confidence: 54%
“…Experiments in rodents, cats, and primates have mapped the immunohistochemical profile and the afferent topography of the SC and have demonstrated that the cholinergic innervation of the superficial subdivision originates from the brain stem's parabigeminal nucleus (Feig et al 1992;Graybiel 1978;Hall et al 1989;Mufson et al 1986;Roldán et al 1983) whereas the deep subdivision innervation arises from the parabrachial region, primarily composed of the PPTg and the LDTg (Beninato and Spencer 1986;Graybiel 1978;Hall et al 1989;Harting and Van Lieshout 1991;Illing and Graybiel 1985;Jones and Webster 1988;Ma et al 1991;Stubblefield et al 2015;Wallace and Fredens 1988;Woolf and Butcher 1986). We focus on this latter innervation because the deep subdivision of the SC is directly involved in selecting targets for movements, although the superficial cholinergic input could in turn modulate intralaminar processing within the SC (Ghitani et al 2014;Isa et al 1998;Lee et al 1997).…”
Section: Cholinergic Input To Superior Colliculus From Parabrachial Rmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the superior colliculus (SC) plays a critical role in selecting the action – a leftward or rightward orienting movement – required by this task ( Felsen and Mainen, 2008 , 2012 ; Stubblefield et al, 2013 ), consistent with its role in selecting orienting movements in other species ( Glimcher and Sparks, 1992 ; Horwitz and Newsome, 2001 ; Bergeron et al, 2003 ; Krauzlis et al, 2004 ; Song et al, 2011 ; Wolf et al, 2015 ). In this study, we asked whether the pedunculopontine tegmental nucleus (PPTg), a mesencephalic sensorimotor hub that provides direct input to the SC ( Graybiel, 1978 ; Beninato and Spencer, 1986 ; Stubblefield et al, 2015 ), encodes information about recent actions and their outcomes by recording from individual neurons in behaving mice. While numerous regions provide input to the SC ( Sparks and Hartwich-Young, 1989 ), many of which may modulate its processing underlying action selection ( Wolf et al, 2015 ), the PPTg holds particular interest because it is engaged by sensorimotor tasks across species ( Matsumura et al, 1997 ; Dormont et al, 1998 ; Kobayashi and Isa, 2002 ; Kobayashi et al, 2002 ; Okada and Kobayashi, 2009 ; Norton et al, 2011 ; Thompson and Felsen, 2013 ; Lau et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…2D). Detailed training stages for IS trials are described in Lintz & Felsen (Stubblefield et al, 2013;Stubblefield et al, 2015;Lintz and Felsen, 2016). Mice 178 performed 5 blocks (SG, IS, SG, IS, SG) per session (Fig.…”
mentioning
confidence: 99%